The Role of the Extracellular Matrix in Neural Progenitor Cell Proliferation and Cortical Folding During Human Neocortex Development - Long, Katherine R.; Huttner, Wieland B. (Frontiers in Cellular Neuroscience, 2022)
Extracellular matrix (ECM) has long been known to regulate many aspects of neural development in many different species. However, the role of the ECM in the development of the human neocortex is not yet fully understood. In this review we discuss the role of the ECM in human neocortex development and the different model systems that can be used to investigate this. In particular, we will focus on how the ECM regulates human neural stem and progenitor cell proliferation and differentiation, how the ECM regulates the architecture of the developing human neocortex and the effect of mutations in ECM and ECM-associated genes in neurodevelopmental disorders.